Peranan Media Sosial Facebook dalam Meningkatkan Komunikasi Pemasaran di Era Digital - Ayu Oktaviani; Anwar Maulana; Ricky Firmansyah (MUKASI: Jurnal Ilmu Komunikasi, 2023)
In the digital era, communication and information technology are increasingly developing which allows digital development to progress very rapidly by developing technology. Making communication in marketing more effective. Therefore, marketing communication is a facility used by entrepreneurs to influence consumers' increase in the product or brand offered directly or indirectly and becomes a statement about the product or brand. In addition, in marketing marketing communications are needed to foster buyer understanding of the goods offered, to increase sales results, and to make goods sell quickly. Therefore, this research aims to understand the role of Facebook social media in marketing communications in the current digital era. The method used in this research is qualitative with analysis and approaches to obtain data information. The results obtained in this study are that Facebook social media plays an important role for communication in the current digital era, this is due to the wide reach that is obtained and the many features that facilitate sales so that marketing carried out by people can be effective and quickly reach their target market.